STUDI BANDING PERANGKAT LUNAK APLIKASI GANESHA DIGITAL LIBRARY (GDL) SEBAGAI REPOSITORY INSTITUSI BERBASIS OPEN SOURCE - Ilham Arnomo (JURNAL TEKNIK INFORMATIKA, 2019)
The purpose of the research is to analyze the technical features of the Ganesha Digital Library (GDL) application with DSpace and Eprints, so that it will be proved technically whether the GDL application can meet the standards and criteria as the application software repository institution ?. Using experimental approach research methods by installing GDL, DSpace and Eprints application to further analyze and compare the technical features of the three applications. The results show that GDL application meet standards and criteria as institutional repository application, since they have most of the technical features of institutional repositories including the features of the OAI-PMH (Open Archives Initiative Protocol for Metadata Harvesting); has a dublincore metadata standard; and has been licensed to open source (General Public License) GPL that is needed for the utilization, use and development of institutional repository applications according to the needs of a college institution.